ADOPTION OF WHATSAPP AND TELEGRAM IN INDIA. - KARUNKARAN, S.; SANTHIYA, M.; HARSINY, E.; MOVIGA, B.; NIVEDHITHA, T. M. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Social media has become a vital source of communication worldwide from human-to-human, human-to-machine, machine-to-machine and machine-to-human. Different forms of these communications have a variety of quality parameters and they are used in various application scenarios. Earlier started as a text exchange medium now has support for all forms of digital media. Race in computing speed and communication bandwidth leverage the growth of the social media. Particularly in India the revolution started when Orkut entered the market in 2007. Even though there was constraint in latest hardware technology and network bandwidth in India, the huge market place it has attracted developers to tune their applications for the available technological resources here. Today there are quite a good number of social media competitors in India. Features offered to customers by these social media vary in spite of their growth. People have different choices to use with. This article analyzes the penetration performance of WhatsApp and Telegram in India. The focus is to create technology awareness among the users of these two competitors.